2008
DOI: 10.1039/b811886h
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of tetraphenylporphyrin monoacids by ion-transfer voltammetry at polarized liquid|liquid interfaces

Abstract: We present a simple methodology to illustrate the existence of tetraphenylporphyrin monoacid based on ion-transfer voltammetry at a polarized water|1,2-dichloroethane interface and organic pK values are also estimated.The acid-base property of free-base porphyrins has been widely investigated, but the subject is still the matter of some controversy. 1 The tetrapyrrole ring of a free-base porphyrin contains two tertiary nitrogen atoms, which allows the gain of protons to form a monoacid and a diacid, as illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 9 publications
3
25
0
Order By: Relevance
“…The same shift was reported for the voltammetric peaks of the facilitated proton transfer (Fig. 1, solid red line) [13]. Indeed, the halfwave potential difference D Fig.…”
Section: Resultssupporting
confidence: 82%
“…The same shift was reported for the voltammetric peaks of the facilitated proton transfer (Fig. 1, solid red line) [13]. Indeed, the halfwave potential difference D Fig.…”
Section: Resultssupporting
confidence: 82%
“…1 in Ref. [28] and as confirmed in the present study, pK DCE a1 and pK DCE a2 were found to be equal to 6.0 and 9.8 using TB À as the organic counter anion, and 6.7 and 10.3 when using TPBCl À as the organic counter anion [29] showing the influence of the organic supporting electrolyte in the basic properties of the porphyrin with …”
Section: Resultssupporting
confidence: 87%
“…To determine the apparent assisted ion transfer potential of H + , the scan rate dependence of the cyclic voltammetry together with the concentration dependence were extrapolated to zero scan rate and peak to peak separation of approximately 60 mV was observed (see SI of [28]). The diffusion coefficient obtained from the scan rate and the concentration dependence were both found to be equal to 6. , respectively, can be estimated by exploring the pH dependence presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the interest to the chemistry of natural and synthetic porphyrins is continuously increased. However, the many properties of porphyrin were investigated only on the qualitative level due to the low solubility of porphyrins in the most solvents, [1] the formation of supramolecular aggregates, [2] the specific of adsorbed behavior at the interface, [3] etc. The porphyrins can include the several reaction centers and different substituents which allow changing its chemical activity and other properties.…”
Section: Introductionmentioning
confidence: 99%